Vasomotor symptom characteristics: are they risk factors for incident diabetes?. Issue 5 (May 2018) - Gray, Kristen E.; Katon, Jodie G.; LeBlanc, Erin S.; Woods, Nancy F.; Bastian, Lori A.; Reiber, Gayle E.; Weitlauf, Julie C.; Nelson, Karin M.; LaCroix, Andrea Z.
Abstract: Objective: Vasomotor symptoms (VMS), encompassing hot flashes and night sweats, may be associated with diabetes, but evidence is limited. We sought to estimate these associations. Methods: Among 150, 007 postmenopausal Women's Health Initiative participants from 1993 to 2014, we prospectively examined associations of incident diabetes with VMS characteristics at enrollment: any VMS, severity (mild/ moderate/severe), type (hot flashes/night sweats), timing (early [premenopausal or perimenopausal]/late [postmenopausal]), and duration. Cox proportional-hazards models estimated hazard ratios (HRs) and 95% confidence intervals (CIs). Results: Mean duration of follow-up was 13.1 years. VMS prevalence was 33%. Reporting any VMS was associated with 18% increased diabetes risk (95% CI 1.14, 1.22), which increased with severity (mild: HR 1.13, 95% CI 1.08, 1.17; moderate: HR 1.29, 95% CI 1.22, 1.36; severe: HR 1.48, 95% CI 1.34, 1.62) and duration (4% per 5 years, 95% CI 1.03, 1.05), independent of obesity. Diabetes risk was more pronounced for women reporting any night sweats (night sweats only: HR 1.20, 95% CI 1.13, 1.26; night sweats and hot flashes: HR 1.22, 95% CI 1.17, 1.27) than only hot flashes (HR 1.08, 95% CI 1.02, 1.15) and was restricted to late VMS (late: HR 1.12, 95% CI 1.07, 1.18; early and late: HR 1.16, 95% CI 1.11, 1.22; early: HR 0.99, 95% CI 0.95, 1.04). Conclusions: VMS are associated with elevated diabetes risk, particularly for women reporting night sweats and postmenopausal symptoms. The menopause transition may be an optimal window for clinicians to discuss long-term cardiovascular/metabolic risk with patients and leverage the bother of existing symptoms for behavior change to improve VMS and reduce diabetes risk. Abstract : Supplemental Digital Content is available in the text